Exploring the Neuroprotective Mechanism of Curcumin Inhibition of Intestinal Inflammation against Parkinson's Disease Based on the Gut-Brain Axis - Lifan Zhong; Benchi Cai; Qitong Wang; Xi Li; Wendi Xu; Tao Chen (MDPI AG, 2022)
Parkinson's disease (PD) is a chronic progressive neurodegenerative disease commonly seen in aged people, in which gastrointestinal dysfunction is the most common nonmotor symptom and the activation of the gut-brain axis by intestinal inflammation may contribute to the pathogenesis of PD. In a previous study, curcumin was considered neuroprotective in PD, and this neuroprotective mechanism may act by inhibiting intestinal inflammation. Therefore, the aim of this study was to evaluate the effect of curcumin on motor dysfunction and the loss of dopaminergic neurons in a PD mouse model, induced by N-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) using open field test and pole test behavioral assessments and the immunofluorescence and Western blot methods. Moreover, the effects of curcumin on gastrointestinal dysfunction, gastric barrier function, pro-inflammatory cytokines, and the SIRT1/NRF2 pathway in intestinal tissues in a PD mouse model were assessed using fecal parameters and intestinal dynamics, immunofluorescence, ELISA, and Western blot. A motor impairment study of an MPTP-induced mouse group prior to treatment with curcumin had a lower total movement distance and a slow average speed, while there was no statistical difference in the curcumin group. After treatment with curcumin, the total movement distance and average speed improved, the tyrosine hydroxylase (TH) rate in the substantia nigra pars compacta (SNpc) and striatum were reduced, the pyroptosis of AIM2 and caspase-1 activations were inhibited, and intestinal inflammatory factors and intestinal inflammation were reduced. Curcumin improved gastrointestinal disorders and gastrointestinal barrier function in the MPTP-induced mice and reversed MPTP-induced motor dysfunction and dopaminergic neuron loss in mice. The above effects may be partly dependent on curcumin activation of the SIRT1/NRF2 pathway in the colon. This study provides a potential opportunity to develop new preventive measures and novel therapeutic approaches that could target the gut-brain axis in the context of PD and provide a new intervention in the treatment of Parkinson's disease.